Understanding Baroreflex Regulation of Blood Pressure from a Patient with Autonomic Failure - Elapulli Sankaranarayanan Prakash (Association of American Medical Colleges, 2015)
Abstract This resource is a case study of a patient with autonomic failure, written to facilitate an understanding of baroreflex regulation of blood pressure and a number of related concepts. The main patient encounter in it was written to be one in a series of a dozen other case scenarios in the cardiovascular block of an integrated organ system and case-based curriculum for second-year medical students. It has been implemented once for a class of second-year medical students, and the materials included here have been reviewed and updated based on the experience of its implementation. This resource includes an instructor's guide, the case itself, a student guide, and a few mini-cases (i.e., problem-solving exercises) that may be used following the discussion of the case to assess if the learner's understanding of concepts in the case transfer to similar contexts. Additionally, there are materials that are intended for instructors only, including a brief analysis of the case, a discussion of the case formatted as questions and answers, answers to follow-up problem-solving exercises, and a list of references consulted in the preparation of this resource. Effectiveness of this case was not formally assessed per se. My personal experience facilitating discussions of this case for a group of seven second-year medical students in the cardiovascular phase of the curriculum was good, and I believe students found discussing this case to be helpful in working on learning objectives of the cardiovascular phase. The case appeared to function very well as a tool to promote problem solving ability in this domain.